2002
DOI: 10.1161/hc0902.105718
|View full text |Cite
|
Sign up to set email alerts
|

Increased Prevalence of Carotid Atherosclerosis in Hepatitis B Virus Carriers

Abstract: Background-Recent experimental and epidemiological findings suggest that some infectious agents play a role in the development and promotion of atherosclerosis. We have investigated the possible association between hepatitis B virus surface antigen (HBsAg) positivity and carotid arteriosclerosis. Methods and Results-In this cross-sectional cohort study, we analyzed data from subjects undergoing general health-screening tests, including both high-resolution B-mode carotid ultrasound and assessment of HBsAg stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
77
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(84 citation statements)
references
References 17 publications
3
77
0
4
Order By: Relevance
“…33,35 Recently, and HBx-TG mice, and they were analyzed for protein levels by western blotting (top). The density of each protein band was determined with an image analysis system and normalized to that of the corresponding ␣-tubulin.…”
Section: Discussionmentioning
confidence: 99%
“…33,35 Recently, and HBx-TG mice, and they were analyzed for protein levels by western blotting (top). The density of each protein band was determined with an image analysis system and normalized to that of the corresponding ␣-tubulin.…”
Section: Discussionmentioning
confidence: 99%
“…8 Similarly, in a recent study Yang et al found no association between HBsAg seropositivity and increased carotid atherosclerosis in Taiwanese. 16 However, in a cross-sectional cohort study including 4,686 subjects of whom 1,294 (28%) had carotid atherosclerosis and 40 (0.9%) had HBsAg seropositivity, Ishizaka et al 17 suggested the possible role of chronic HBV infection in the pathogenesis of carotid atherosclerosis. Some possible mechanisms to explain the relationship between HBV infection and atherosclerosis have been suggested.…”
Section: Association Between Viral Infectious Agents and Atherosclerosismentioning
confidence: 99%
“…[1][2][3][4] However, it is unclear whether atherogenesis is associated with any infection that provokes activation of inflammatory processes or whether only specific organisms play an important role. 3,5 Moreover, some studies reporting no association between markers of infection and atherosclerosis cast doubt on their role.…”
mentioning
confidence: 99%